IL-23 Inhibition in Ankylosing Spondylitis: Where Did It Go Wrong? - Baeten, Dominique; Adamopoulos, Iannis E. (Frontiers in Immunology, 2021)
Axial spondyloarthritis is a prevalent form of chronic arthritis which is related to psoriatic arthritis and skin psoriasis. TNF and IL-17A as well as IL-17F are key cytokines contributing to the pathobiology of this disease, as evidence by the therapeutic efficacy of inhibition of these factors. Despite the evidence that IL-23 acts as an upstream driver of Th17 cells, the T lymphocytes producing IL-17, and that IL-23 inhibition shows profound efficacy in psoriasis, blocking IL-23 failed to show any evidence of clinical efficacy in axial spondyloarthritis. In this viewpoint article, we revisit the reasons-to-believe in a role of IL-23 in the pathobiology of axial spondyloarthritis, discuss what we have learned on the pathobiology of this disease in general and on the function of the IL-23/IL-17 axis in particular, and share a handful of lessons learned that are of relevance for the translation of emerging biological insights into clinical therapeutics.